A study of unclaimed bodies autopsied at AIMS, B.G. Nagara: a retrospective study - Mahadeva, Rakshitha Balenahalli; Kakanna, Lokesh; Yelauri, Chinmayi; Gowda, Vijay Kumar Aralapura Govinde (International Journal of Research in Medical Sciences, 2025)
Background: An unidentified dead body always presents a challenge for forensic specialists and investigating officers. However, when a deceased person is found in a disfigured, skeletonized or decomposed state, the identification process becomes significantly more difficult and stressful for forensic professionals. The objective of this study was to examine the demographic patterns in cases of unidentified bodies found in and around AIMS B.G. Nagar, India. Methods: A retrospective cross-sectional study was performed on 84 cases of unidentified deceased individuals brought for post-mortem examination at the department of forensic medicine and toxicology, AIMS, in B.G. Nagar, Karnataka, between January 2021 and December 2024. To maintain consistency in data collection, a standard proforma was utilized, focusing on unidentified bodies and excluding identified cases. Results: Over the study period, 796 necropsies were performed, of which 84 cases (10.55%) involved unidentified bodies. Of these, 25 cases (29.76%) were identified, while the remaining cases stayed unidentified. The highest number of deceased individuals were in the 41–50 age group, with the majority being male. November saw an increase in deaths, accounting for 11 cases (13.1%). Additionally, 39 cases (46.4%) were found at bus stops, highways and roads. The primary cause of death was natural, with disease and pathological conditions responsible for (60.7%) of the fatalities. Conclusions: This study highlights the common causes of death in the study area and emphasizes the necessary public health measures to be taken.